Breeding of Andean bean type for Panama: Results of a PROFRIJOL project. 1993-1996. - Rodríguez, Emigdio (2015)
Native germplasm of a Panama common bean was evaluated in order to obtain its morphologic characteristics and compare them with a group of lines and varieties of CIAT’s breeding program. The purpose was to find a germplasm that could surpass native varieties in terms of its resistance to Web Blight, yield, growing habits, and grain color. A randomized complete block design was used. Five promising lines for commercial use were selected based on yield, resistance to Web Blight, growth pattern, and grain color criteria. Three bean lines are undergoing validation trials in farms.